Responding to the Challenge of Fragility and Security in West Africa : Natural Resources, Extractive Industry Investment, and Social Conflict - Maconachie, Roy; Srinivasan, Radhika; Menzies, Nicholas (World Bank, Washington, DC, 2015)
The inability to unlock natural resource wealth for the benefit of developing countries’ local populations, a phenomenon popularly known as the ‘resource curse’ or the ‘paradox of plenty’, has spawned extensive debate among researchers and policy makers in recent years. There is now a well-established body of literature exploring the links between natural resources and conflict, with some sources estimating that over the past 60 years, 40 percent of civil wars have been associated with natural resources. Following this introduction, Section two provides an overview of interstate tensions in West Africa in order to improve understanding of the drivers of fragility that trigger conflict between countries around extractive industry investment. Here, the discussion is grounded in examples in which interstate tensions have been apparent, including the case of the Mano River Union, Cote d’Ivoire, Guinea, Liberia, and Sierra Leone, a region with a history of conflict, and where the exploitation of commercial deposits of high-value resources may continue to have a potentially destabilizing effect. Section three focuses on the decentralization of natural resource revenues, a process that proponents believe can help manage grievances and defuse intrastate tension in areas directly affected by resource extraction, but one that is also not without challenges. Drawing upon the case of Ghana’s Mineral Development Fund, the section explores the potential for conflict (and conflict triggers) to arise when the redistribution of extractive industry revenues to subnational regions takes place. In doing so, it becomes apparent that the capture and misuse of revenues from the fund is as much a political issue as it is a policy or technical one. This sets the stage for section four, which focuses in greater detail on extractive industry-related conflict within catchment communities, and how contestation is most often a result of unequal power relationships. Section five, the conclusion, summarizes and reflects upon some of the challenges and struggles over resource management associated with West Africa’s recent resource boom, and draws out some of the cross-cutting themes. Here, suitable entry points for future lines of inquiry and engagement are identified.